Two foundation deposits in a domestic context at Tell el-Ghaba (early Saite Period, Eastern Delta, Egypt) - Crivelli, Eduardo Adrian (2013)
Two foundation deposits were discovered at a private construction at Tell el-Ghaba, a first millennium settlement located in what was once the Eastern Delta. The creation of these deposits seems to have been a rather uncommon practice in domestic contexts. In this paper, the contents of the deposits are described, and comparisons are made. The presence of Egyptian and imported pottery and hints of a weaving practice that had already developed in the Southern Levant suggest the presence of foreign people or, at least, a foreign influence at this site.